Fishes of the Atlantic Rainforest of Boraceia: testimonies of the Quaternary fault reactivation within a Neoproterozoic tectonic province in Southeastern Brazil - Ribeiro, A. C.; Lima, FCT; Riccomini, C.; Menezes, N. A. (Verlag Dr. Friedrich Pfeil, 2006)
The upper portion of the Rio Guaratuba, located in the Serra do Mar coastal range of Southeastern Brazil, shows biological and geological evidences of being captured and diverted away from its original course in the direction of the Parana River Basin to become a coastal river due to the Quaternary activity of NW-trending faults. Despite draining directly to the Atlantic Ocean, the upper portion of the Guaratuba still maintains an ichthyofauna that is typical of the adjoining Parana River Basin rather than the characteristic fish fauna of the Brazilian coastal drainages. The fish fauna of the upper Guaratuba is an evident testimony of the tectonic process that allowed the faunal interchange between the upland basins and the coastal drainages that probably has been taking place in Southeastern Brazil throughout the long geological history of the passive Brazilian continental margin.